Analysis of the Treatment of Periarthritis of Shoulder with Fire Needle Combined with Cupping Therapy (Journal of research in medical and health sciences, 2026)
Objective: This article explores the clinical efficacy of the combined therapy of fire needle and cupping in the treatment of periarthritis of the shoulder by analyzing the treatment process of patients with periarthritis of the shoulder who received this therapy. Methods:A combined therapy of fire needling and cupping was applied to patients with shoulder periarthritis, and the treatment process and effects were analyzed. Results:After 4 weeks of treatment, the patient's shoulder and joint pain significantly reduced, the range of motion improved significantly, and the quality of life improved as well. Conclusion:The combination therapy of fire needling and cupping is currently a highly recommended treatment method in clinical practice. It is effective for shoulder periarthritis and can significantly alleviate pain and improve the mobility of the shoulder joint.
Keywords: Ignipuncture; Cupping; Scapulohumeral periarthritis; Activity functions